Association between ventilatory efficiency, oxygen uptake, and Glittre-ADL test results in patients with chronic heart failure: a preliminary study - Hebert Olímpio Júnior (BMC Research Notes, 2021)
Abstract Objective The Glittre-ADL test (GA-T) is a functional capacity test that stands out for encompassing multiple tasks similar to activities of daily living. As ventilatory efficiency is one of the variables valued in the prognosis of chronic heart failure (CHF), this study aimed to evaluate associations between functional capacity and ventilatory variables in patients with CHF during the GA-T. Results Eight patients with CHF and New York Heart Association (NYHA) functional classification II–III underwent the GA-T coupled with metabolic gas analysis to obtain data by means of telemetry. The median total GA-T time was 00:04:39 (00:03:29–00:05:53). Borg dyspnoea scale scores before and after the GA-T were 2 (0–9) and 3 (1–10), respectively (P = 0.011). The relationship between the regression slope relating minute ventilation to carbon dioxide output (VE/VCO2 slope) was correlated with the total GA-T time (rs = 0.714, P = 0.047) and Borg dyspnoea score (rs = 0.761, P = 0.028). The other ventilatory variables showed no significant correlations. Our results suggest that the total GA-T time can be applied to estimate the ventilatory efficiency of patients with CHF. Future studies may use the GA-T in conjunction with other functional capacity tests to guide the treatment plan and evaluate the prognosis.